Model to increase the profitability of micro and small businesses through the digital transformation of contact channels using Sales Funnels and Adaptive Sales in the post-COVID-19 era - Andrea del Rocio, Arroyo Elescano (2023)
Commercial enterprises carry out activities in which goods or services are exchanged for money, which allows them to keep operating by recovering their investment to continue producing goods or services, thus promoting the growth of the economy; This process feeds the generation of employment, satisfaction of consumer needs and development of products and services of societies. Of the total number of commercial organizations operating in the world, 90% are micro, small and medium-sized enterprises (MSMEs), and in the Peruvian case the importance of this type of companies is even greater since they represent 85% of employment and contribute to 84% of the Gross Domestic Product (GDP); Specifically, micro and small enterprises represent 95.8% of the country's companies. However, despite their importance, only 10% of these companies manage to pass the 10-month operating period, due to their low level of competitiveness. There are several factors that affect this performance, however, it has been identified that 90% of companies consider that in order to operate properly they must develop marketing and sales processes supported by digital businesses. To overcome these deficiencies, it has been established as the main objective in the following research to implement an agile and efficient model based on customer segmentation and adaptive sales generation using Digital Transformation with the aim of improving sales, reducing customer service times, improving customer acquisition and customer development, through efficient management processes.